MiR-Synth: a computational resource for the design of multi-site multi-target synthetic miRNAs. Issue 9 (13th March 2014) - Laganà, Alessandro; Acunzo, Mario; Romano, Giulia; Pulvirenti, Alfredo; Veneziano, Dario; Cascione, Luciano; Giugno, Rosalba; Gasparini, Pierluigi; Shasha, Dennis; Ferro, Alfredo; Croce, Carlo Maria
Abstract: RNAi is a powerful tool for the regulation of gene expression. It is widely and successfully employed in functional studies and is now emerging as a promising therapeutic approach. Several RNAi-based clinical trials suggest encouraging results in the treatment of a variety of diseases, including cancer. Here we present miR-Synth, a computational resource for the design of synthetic microRNAs able to target multiple genes in multiple sites. The proposed strategy constitutes a valid alternative to the use of siRNA, allowing the employment of a fewer number of molecules for the inhibition of multiple targets. This may represent a great advantage in designing therapies for diseases caused by crucial cellular pathways altered by multiple dysregulated genes. The system has been successfully validated on two of the most prominent genes associated to lung cancer, c-MET and Epidermal Growth Factor Receptor (EGFR). (See http://microrna.osumc.edu/mir-synth ).